2021
DOI: 10.5194/isprs-annals-viii-4-w1-2021-105-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ipad Pro 2020 Lidar for Estimating Tree Diameters in Urban Forest

Abstract: Abstract. Remote Sensing (RS) techniques are increasingly used in urban tree inventory measurements for their improved accuracy and promptness over the conventional methods. The focus of this study is to evaluate the application of iPad Pro 2020 and its LiDAR sensor for urban trees reconstruction and Diameter at Breast Height (DBH) measurements. Altogether, 101 trees were scanned. We have used individual- and multiple-tree scan modes with different settings (Resolution: 10 mm, 15 mm, 20 mm; Confidence: High, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The second most accurate results were obtained from TLS, with values close to the reference of 1.3 ± 1.6 cm (c.f Table 3). Nevertheless, the Azure Kinect DBH measurements were more accurate when compared to the best results obtained with the iPad Pro 2020 (σ = ±2.78cm) in this study (Wang et al, 2021). Our results confirmed that the Azure Kinect has a very good potential in the field of low-cost precision sensors.…”
Section: M3c2 (Multiscale Model To Model Cloud Comparison)supporting
confidence: 82%
“…The second most accurate results were obtained from TLS, with values close to the reference of 1.3 ± 1.6 cm (c.f Table 3). Nevertheless, the Azure Kinect DBH measurements were more accurate when compared to the best results obtained with the iPad Pro 2020 (σ = ±2.78cm) in this study (Wang et al, 2021). Our results confirmed that the Azure Kinect has a very good potential in the field of low-cost precision sensors.…”
Section: M3c2 (Multiscale Model To Model Cloud Comparison)supporting
confidence: 82%
“…The same set was also used to capture the video with the IPAD Pro (Apple) and experiment with the Lidar instrument, testing different working distances and configurations (Table 1). The low resolution obtained from the Lidar did not allow for acceptable results (Figure 5), justifying the previous research on the topic (Luetzenburg et al, 2021;Wang et al, 2021).…”
Section: Data Acquisitionmentioning
confidence: 50%
“…A small insight should also be devoted to introducing Lidar systems integrated with computer vision algorithms in some devices, such as IPADs and iPhones of the latest generation. Although these are very powerful and versatile tools, early experiments showed how they had been created mainly to support other tools, such as Augmented Reality (Luetzenburg et al, 2021;Wang et al, 2021). On the image-matching side, it is essential to highlight the increasingly optimized use of uncalibrated cameras mounted on smartphones for defining reliable complex 3D models (Russo et al, 2019), as well as the application of spherical images to analyse complex environments (Prizeman and Barazzetti, 2021).…”
Section: State Of the Artmentioning
confidence: 99%
“…This study achieved an overall RMSE of 1.5 cm (8.6%) for DBH values estimated from iPad Pro LiDAR data for 15 sites in the boreal forest. This is a lower RMSE than those reported in several previous studies using the iPad Pro to estimate DBH, such as: an urban park (Slovakia), 2.8 cm (7.0%) and 5.2 cm (13.0%); a research forest (Austria), 3.1 cm (10.5%) and 6.3 cm (21.2%); natural and plantation forests (Japan), 2.3 cm (10.5%); and, a university campus (Turkey), 2.3 cm (11.7%) [5,[22][23][24]. A previous study using the same methodology as used in this study reported an RMSE of 1.1 cm (6.2%) for a plantation forest in Canada [11].…”
Section: Discussionmentioning
confidence: 99%